# math- Algebra 2

posted by .

I have absolutely no idea how to do this please help!
Find the sum:
it has the sigma sign with 12 at the top, (10k-8)(6k+7) in the middle and k=1 at the bottom

• math- Algebra 2 -

It just means, add:

the value of (10k-8)(6k+7) when k=1
plus
the value of (10k-8)(6k+7) when k=2
plus
the value of (10k-8)(6k+7) when k=3
plus
... (and so on, 4, 5, to 9, 10)...
the value of (10k-8)(6k+7) when k=11
plus
the value of (10k-8)(6k+7) when k=12

So you could just do it by calcuating out:

the value of (10k-8)(6k+7) when k=1 is 26
plus
the value of (10k-8)(6k+7) when k=2 is 228

and so on.

It mightn't be a bad idea to do that anyway, since you will understand it thoroughly and be sure of your answer.

However, there are short-cuts.

It may be that you've already covered these in your class, or it may be that you were given this exercise so that you'll appreciate them when you do cover them! :-)

There is a formula for the sum of x from 0 to n and a formula for the sum of x^2 from 0 to n. You can probably find them in your text.

By multiplying out the expression, we can then use those formulas.

• math- Algebra 2 -

all right great thank you so much!

• math- Algebra 2 -

You're welcome!

## Respond to this Question

 First Name School Subject Your Answer

## Similar Questions

1. ### Algebra

find the indicated sum not sure how to type the sigma sign, but here is the problem 6 on top of the sigma sign. under the sigma sign is i=3 and on the right side of the sigma sign (3i-2)
2. ### algebra

find the indicated sum 4 on top of sigma symbol i=1 on the bottom of sigma symbol 3^i on the right side please help me figure this out
3. ### Maths

Express the sum using summation notation: 1 - 1/2 + 1/3 - 1/4 + 1/5 - ... (to 3n terms) If I'm doing this right so far, with k=1 (the number on bottom of the sigma), the equation after the sigma would be ((-1)^(k+1)) / k I'd be able …
4. ### Maths

Express the sum using summation notation: 1 - 1/2 + 1/3 - 1/4 + 1/5 - ... (to 3n terms) If I'm doing this right so far, with k=1 (the number on bottom of the sigma), the equation after the sigma would be ((-1)^(k+1)) / k I'd be able …
5. ### Algebra II

Please help-I need to write 4+6+8+10 in sigma notation would it be sigma sign in middle (3) on top of sign, n=0 on bottom of signma notation and to the right it would be (4+2n) so it would look like-- (3) (sigma in middle) (4+2n) n=0
6. ### Pre-Calc-Please check

1.Write 4+6+8+10 in sigma notation: I came up with sigma in the middle 3 on top j=0 on the bottom 2. Find the 10th term of the sequence -1/5,-1/20,-1/80 this was a geometric sequence so I said a(subscript10) = -1/5*1/4^(10-1) =-1/5*(1/4)^9 …
7. ### Pre-Calc-Please check answer

1.Write 4+6+8+10 in sigma notation: I came up with sigma in the middle 3 on top j=0 on the bottom 2n+4 to the right of the signma sign 2. Find the 10th term of the sequence -1/5,-1/20,-1/80 this was a geometric sequence so I said a(subscript10) …
8. ### Pre-Calc-Please check answer

1.Write 4+6+8+10 in sigma notation: I came up with sigma in the middle 3 on top j=0 on the bottom 2n+4 to the right of the signma sign 2. Find the 10th term of the sequence -1/5,-1/20,-1/80 this was a geometric sequence so I said a(subscript10) …
9. ### Pre-CalcPlease check

Please check: 1.Write in expanded form: this is a sigma notation- 4 on top signma in middle k=1 on bottom to right of sigma is (k-1)(k-2) I solved: k=1 (1-1)(1-2)=0(-1)=0 K=2 (2-1)(2-2) = 1(0)=0 k=3(3-1)(3-2)=2(1)=2 k=4 (4-1)(4-)=3(2)=6 …
10. ### Pre-Calc-please check

Please check this for me expand (3z-2b)^5 using Binomial Theorem (a+b)^n = n on top sigma in middle k=0 to right (n/k)a^(n-k)b^k (3a-2b)^5 = 5 on top sigma in middle k=0 on bottom(5/k)(3a)^5-k(-2b)^k (5/0)(3a)^5(-2b)^0+(5/1)(3a)^4(-2b)^1 …

More Similar Questions